Ecological and economic organization of crowning territory and arrangement of existing land in the Right-bank Forest-and-Steppe of Ukraine - V. Kyryliuk; P. Borovyk; Y. Kyselov; O. Kyseliova (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2022)
The article analyzes the current land use of Dzendzelivske LLC of Mankivka village community of Uman district of Cherkasy region (former Dzendzelivska village council), which showed that the agro-ecological condition of agricultural lands before the project was in deteriorating condition and required sound land use solutions.